2022
DOI: 10.3390/foods11040570
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Extracts from Black Chokeberry, Cranberry, and Pomegranate to Identify Compounds That Influence Lipid Metabolism

Abstract: Polyphenols show a spectrum of bioactive effects, including an influence on lipid metabolism. In this study, we performed activity-guided fractionations of black chokeberry (aronia), cranberry, and pomegranate extracts to identify the biologically active compounds. The extracts were prepared from fruit juice concentrates with the adsorbent resin Amberlite XAD-7 and were separated into a copigment and an anthocyanin fraction, followed by fractionation into a polymer and monomeric fraction by means of hexane pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Cochrane's risk-of-bias tool for randomized trials is a standard tool used to evaluate the quality of RCTs [18]. Two authors individually assessed each included study using the following seven main aspects of the Cochrane risk-of-bias tool one by one: (1) random sequence generation (selection bias); (2) allocation concealment (selection bias); (3) blinding of participants and personnel (performance bias); (4) blinding of outcome assessment (detection bias); (5) incomplete outcome data (attrition bias); (6) selective reporting (reporting bias); (7) other bias. Based on the evaluation criterion of Cochrane's recommendations, the overall risk-of-bias judgment of each aspect was classified as "high risk", "unclear risk", and "low risk".…”
Section: Quality Assessment Of Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Cochrane's risk-of-bias tool for randomized trials is a standard tool used to evaluate the quality of RCTs [18]. Two authors individually assessed each included study using the following seven main aspects of the Cochrane risk-of-bias tool one by one: (1) random sequence generation (selection bias); (2) allocation concealment (selection bias); (3) blinding of participants and personnel (performance bias); (4) blinding of outcome assessment (detection bias); (5) incomplete outcome data (attrition bias); (6) selective reporting (reporting bias); (7) other bias. Based on the evaluation criterion of Cochrane's recommendations, the overall risk-of-bias judgment of each aspect was classified as "high risk", "unclear risk", and "low risk".…”
Section: Quality Assessment Of Meta-analysismentioning
confidence: 99%
“…Individuals with CVD may have changes in insulin sensitivity, glucose tolerance, lipid profiles, and oxidative stress biomarkers [ 6 ]. Polyphenols in cranberry have beneficial properties in the modulation of glucose and lipid metabolism, which has been confirmed in a variety of in vitro experiments and animal models [ 7 , 8 , 9 ]. Niesen et al isolated the active compound of cranberry and found that polyphenols extracted from cranberry inhibited lipid accumulation and promoted lipolysis, which had a positive regulatory effect on lipid metabolism [ 7 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Vaccinium is beneficial in reducing adipose tissue inflammation in models of metabolic syndrome [106][107][108][109]. In addition, dried bilberry (Vaccinium myrtillus L.) slowly reduces serum cholesterol and delays the adverse consequences of high-fat diet-induced lipid and glucose metabolism caused by high-fat diet [110].…”
Section: Experimental Study On Diabetes Mellitus and Diabetic Microva...mentioning
confidence: 99%
“…Natural antioxidants can be extracted from plants, for example cranberries and pomegranates. Cranberry extract is highly ranked for its antioxidant quality and quantity [Niesen et al, 2022;Tsirigotis-Maniecka, 2020]. Its antioxidant activity is attributed to the interdependent actions of its organic acids, carbohydrates, and flavonoids.…”
Section: Introductionmentioning
confidence: 99%